Single-Molecule Fluorescence Imaging Reveals GABAB Receptor Aggregation State Changes - Luo, Fang; Qin, GeGe; Wang, Lina; Fang, Xiaohong (Frontiers in Chemistry, 2022)
GABAB receptor is a typical G protein coupled receptor and its functional impairment is related to a variety of diseases. While the premise of GABAB receptor activation is the formation of heterodimer, the receptor can also form tetramer on the cell membrane. Thus it is important to study the effect of GABAB receptor aggregation state on its activation and signaling. In this study, we have applied single-molecule photobleaching step counting and single-molecule tracking methods to investigate the formation and change of GABAB dimers and tetramers. Single-molecule stoichiometry assay of the wide-type and mutant receptors revealed the key sites on the interface of ligand binding domains of the receptor for its dimerization. Moreover, we found the receptor showed different aggregation behaviors at different conditions. Our results offered new evidences for a better understanding of the molecular basis for GABAB receptor aggregation and activation.